Challenges to inerrancy a theological response - Lewis, Gordon Russell, 1926-; Demarest, Bruce A. (Chicago, IL Moody, 1984)
Includes bibliographical references and indexes.
Keywords: Bible -- evidences, authority, etc. -- addresses, essays, lectures